Psychometric analysis of the Inventory of Suicide Orientation ISO-19, in scholarized adolescents - Vecco, Gerardo Ariel; Flores-Kanter, Pablo Ezequiel; Luque, Leticia Elizabeth (Instituto de Investigaciones Psicológicas (IIPSI, Conicet-UNC), 2021)
In terms of prevention, it is desirable to have valid and reliable instruments to detect the risk of suicide. Some psychometric properties of the reduced version of ISO-30 are explored, in a group of 656 school-aged adolescents, 14-20 years old, from Cordoba (Argentina). To evaluate the fit of empirical data to the design identified by Galarza, Fernández-Liporace, Castañeiras, and Freiberg-Hoffmann (2019) for ISO-19, a confirmatory factor analysis (CFA) and exploratory structural equation modeling (ESEM) were performed. Regarding the CFA, the indices for evaluating the model fit were optimal and slightly lower than those obtained using the ESEM model. The quantification of factorial simplicity identified 17 items above the criteria established as acceptable. The elimination of reagents from the original version (ISO-30) and the new identified groupings should be  considered for the global suicide orientation index used in our country.